Study of gene action for yield and quality traits in rice (Oryza sativa L.) - Ch, Sreelakshmi; P, Ramesh Babu (ORYZA-An International Journal of Rice, 2022)
The present experiment was conducted to study the gene action, heterosis, inbreeding depression and heritability for different yield and quality traits in the cross WGL 48684 x IR 36. Analysis of heterosis revealed that most of the traits show duplicate type of epistasis which is non- fixable and cannot be exploited through the general breeding procedures of self pollinated crops. Additive gene effect and complementary epistasis plays a lead role for plant height, number of ear bearing tillers per plant, kernel breadth and amylase content and they can easily be exploited for developing fixed lines. Significant inbreeding depression was found for ear bearing tillers per plant, SPAD Chlorophyll Meter Reading (SCMR), harvest index, grain yield, head rice recovery and kernel elongation ratio. Therefore, few cycles of recurrent selection followed by pedigree method would be effective and useful to utilize all types of gene effects by maintaining considerable heterozygosity through mating of selected plants in early segregating generations.